Levodopa‐induced dyskinesia in Parkinson disease: Sleep matters. Issue 6 (29th November 2018) - Amato, Ninfa; Manconi, Mauro; Möller, Jens C.; Sarasso, Simone; Stanzione, Paolo; Staedler, Claudio; Kaelin‐Lang, Alain; Galati, Salvatore
Abstract : Objective: The spectrum of clinical symptom changes during the course of Parkinson disease (PD). Levodopa therapy, while offering remarkable control of classical motor symptoms, causes abnormal involuntary movements as the disease progresses. This levodopa‐induced dyskinesia (LID) has been associated with abnormal cortical plasticity. Because slow wave activity (SWA) of nonrapid eye movement (NREM) sleep underlies adjustment of cortical excitability, we sought to elucidate the relationship between this physiological process and LID. Methods: Thirty‐six patients at different stages of PD underwent whole‐night video polysomnography–high‐density electroencephalography (vPSG‐hdEEG), preceded by 1 week of actigraphy. To represent the broad spectrum of the disease, patients were divided into 3 groups by disease stage—(1) de novo (n = 9), (2) advanced (n = 13), and (3) dyskinetic (DYS; n = 14)—were compared to an age‐matched control group (n = 12). The SWA‐NREM content of the vPSG‐hdEEG was then temporally divided into 10 equal parts, from T1 to T10, and power and source analyses were performed. T2‐T3‐T4 were considered early sleep and were compared to T7‐T8‐T9, representing late sleep. Results: We found that all groups, except the DYS group, manifested a clear‐cut SWA decrease between early and late sleep. Interpretation: Our data demonstrate a strong pathophysiological association between sleep and PD. Given that SWA may be a surrogate for synaptic strength, our data suggest that DYS patients do not have adequate synaptic downscaling. Further analysis is needed to determine the effect of drugs that can enhance cortical SWA in LID. Ann Neurol 2018;84:905–917